Outcomes of Care by Geriatricians and Non-geriatricians in an Academic Hospital - Merchant, Reshma Aziz; Ho, Vanda Wen Teng; Chen, Matthew Zhixuan; Wong, Beatrix Ling Ling; Lim, Zhiying; Chan, Yiong Huak; Ling, Natalie; Ng, Shu Ee; Santosa, Amelia; Murphy, Diarmuid; Vathsala, Anantharaman (Frontiers in Medicine, 2022)
Introduction.While hospitalist and internist inpatient care models dominate the landscape in many countries, geriatricians and internists are at the frontlines managing hospitalized older adults in countries like Singapore and the United States. The primary aim of this study was to determine outcomes for older patients cared for by geriatricians compared with non-geriatrician-led care team. Methods. Retrospective cohort study of 1,486 Internal Medicine patients aged ≥ 75 years admitted between April and September 2021 was conducted. They were either under geriatrician or non-geriatrician (internists or specialty physicians) care. Data on demographics, primary diagnosis, comorbidities, mortality, readmission rate, Hospital Frailty Risk Score, Age-adjusted Charlson Comorbidity Index, Length of Stay (LOS) and cost of hospital stay were obtained from hospital database and analyzed. Results. The mean age of patients was 84.0 ± 6.3 years, 860 (57.9%) females, 1,183 (79.6%) of Chinese ethnicity and 902 (60.7%) under the care of geriatricians. Patients under geriatrician were significantly older and had higher prevalence of frailty, dementia and stroke, whereas patients under non-geriatrician had higher prevalence of diabetes and hypertension. Delirium as primary diagnosis was significantly higher amongst patients under geriatrician care. Geriatrician-led care model was associated with shorter LOS, lower cost, similar inpatient mortality and 30-day readmission rates but significantly higher 30-day mortality rates. LOS and cost were lower for patients under geriatrician care regardless of frailty status but significant only for low and intermediate frailty groups. Geriatrician-led care was associated with significantly lower extended hospital stay (OR 0.73; 95% CI 0.56 – 0.95) and extended cost (OR 0.69; 95% CI 0.54 – 0.95). Conclusion. Geriatrician-led care model showed shorter LOS, lower cost and associated with lower odds of extended LOS and cost.